Predictive value of neutrophil to lymphocyte ratio for clinical outcome in patients with atrial fibrillation: a systematic review and meta-analysis - Peng, Lei; Liu, Li; Chai, Miaomiao; Cai, Zhonggui; Wang, Deqi (Frontiers in Cardiovascular Medicine, 2024)
The association between the Neutrophil-to-Lymphocyte Ratio (NLR) and the prognosis of Atrial Fibrillation (AF) has been extensively studied, yet clinical outcomes have varied.Consequently, this analysis was undertaken to explore the link between NLR and the prognostic markers of AF.We conducted an exhaustive search across electronic databases, including PubMed, Embase, Web of Science, and the Cochrane Library, to investigate the correlation between the NLR and indicators of adverse clinical outcomes associated with AF from the database establishment date through March 31, 2024. In this study, the recurrence rate of AF was the primary outcome measure, while the secondary outcome measures were mortality, stroke, and left atrial thrombus. Odds ratio (OR), relative risk (RR), hazard ratio (HR) and standard mean difference (SMD) with a 95% confidence interval (CI) were integrated for assessment, and the stability of prognostic outcomes and publication bias were verified by sensitivity analysis and Egger's test, respectively. Subgroup analyses were performed to pinpoint the sources of heterogeneity.Results: This analysis included 20 studies, encompassing a total of 59,256 patients. Our statistical analysis of both categorical and continuous variables revealed that an elevated NLR was significantly associated with increased risks in AF patients for recurrence (categorical variable: OR = 1.39, 95% CI = 1.21-1.60; continuous variable: SMD = 0.49, 95% CI = 0.24-0.74), mortality (categorical variable: OR = 1.87, 95% CI = 1.59-2.20), stroke (categorical variable: OR = 1.56, 95% CI = 1.13-2.17; continuous variable: SMD = 0.77, 95% CI = 0.63-0.91), and left atrial thrombus (categorical variable: OR = 1.87, 95% CI = 1.27-2.75; continuous variable: SMD = 0.59, 95% CI = 0.30-0.89).Subgroup analyses found that high NLR was significantly linked to AF recurrence when the NLR was > 3. High NLR was significantly linked to the risk of stroke in AF when the NLR was ≤ 3.This study suggested that a high NLR is significantly linked to prognostic risk markers of AF, and NLR may be an effective biomarker for the prognosis of AF in clinical practice.